Risk factors of malnutrition in children with congenital heart disease: a meta-analysis - Chen Zhang; Banghong Xu; Cuiying Zhu; Kai Pu; Lanzheng Bian (Frontiers Media S.A., 2024)
BackgroundThe associated factors of malnutrition in children with congenital heart disease (CHD) must be evaluated to provide evidence for the treatment and care of such children.MethodsTwo investigators searched the PubMed database until 25 June 2023 for literature about the associated factors of malnutrition in children with CHD. A meta-analysis of associated factors of malnutrition was performed by RevMan 5.3 software.ResultsThirteen studies involving 8,031 children with CHD were included. Pulmonary hypertension (OR = 3.81, 95% CI: 2.46-4.12), low birth weight (OR = 2.69, 95% CI: 1.25-5.77) and parents' height (OR = 2.15, 95% CI: 1.89-2.92) were the associated factors of growth retardation (all P < 0.05). Pulmonary hypertension (OR = 3.77, 95% CI: 3.13-4.24), low birth weight (OR = 3.04, 95% CI: 2.61-4.18) and pneumonia (OR = 2.35, 95% CI: 2.08-2.83) were the associated factors of low body weight of children with CHD (all P < 0.05).ConclusionsMedical staff should fully understand the risk factors, strengthen nutritional support and enhance nursing care for children with CHD to reduce malnutrition.